Degradation of Cyromazine in Cucumber and Soil - Wang, Hui-Li; Chen, Jin-Hui; Jin, Hui-Fang; Guo, Bao-Yuan; Li, Jian-Zhong (Asian Journal of Chemistry, 2013)
A high performance liquid chromatographic method was developed for the analysis of cyromazine in cucumber and soil to investigate the degradation of cyromazine in the two mediums. The declining kinetics of cyromazine was in accordance to the first order reaction kinetics and the average half-life of cyromazine was 5.2-7.3 days in cucumber, while was 10. 1-15.3 days in soil in three locations of Beijing, Anhui and Hainan of China. The degradation in Beijing was relatively slow and it was higher in Hainan than in other locations. The pro-harvest-interval was 3 days based on the experiments in the three locations and the maximum residual limit of 0.2 mg/kg.